2022
DOI: 10.1088/1741-4326/ac8564
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of the effects of impurity seeding on plasma detachment and impurity screening of snowflake divertor on HL-2M tokamak by SOLPS-ITER

Abstract: To address the issues of mitigation and control of the heat loads on the divertor target, snowflake divertor (SFD) has been proposed on HL-2M tokamak. In this work, simulations have been performed by using SOLPS-ITER to demonstrate the advantages of SFD on HL-2M on plasma detachment and impurity screening during impurity seeding. Firstly, neon (Ne) and argon (Ar) seeding are chosen for comparison in SFD. It is found that Ar seeding significantly mitigates the in-out asymmetry compared with Ne seeding, mainly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…However, the simulation just produces a weak second peak in the particle flux profiles, and does not show a particle flux bifurcation structure near the divertor targets. Thus, much related modeling work is still ongoing [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…However, the simulation just produces a weak second peak in the particle flux profiles, and does not show a particle flux bifurcation structure near the divertor targets. Thus, much related modeling work is still ongoing [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…Seeded impurities have a great impact on divertor plasma and thus change Γ ERO W at targets. When the impurity seeding rate is increased, radiation exhaust caused by impurities is enhanced, which can prompt the achievement of divertor detachment [10,23,24]. Drifts may trigger the movement of the radiation front and affect plasma parameters in the divertor [25,26].…”
Section: Influence Of Ne Puffing Rate On W Transport and Accumulation...mentioning
confidence: 99%
“…SOLPS-ITER code suite with improved numerical solution of the drift terms and the electric potential equation has been applied to study the effect of drifts on the transport of seeded impurities [10,11]. To our best knowledge, the influence of drifts on the transport of sputtered W impurity by SOLPS-ITER still remains unsolved.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments involving N impurity seeding in the HL-2A device revealed that the main factors contributing to divertor detachment are increased neutral pressure and volumetric energy loss [17]. Zhang et al [18]. investigated impurity seeding scenarios in the HL-2M device using SOLPS-ITER simulations and discovered that Ar and Ne impurity seeding leads to increased radiation power in the inner and outer target plate regions, effectively promoting divertor detachment.…”
Section: Introductionmentioning
confidence: 99%